2016
DOI: 10.1089/tmj.2015.0041
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Teens with Asthma in Designing a Patient-Centered Mobile App to Aid Disease Self-Management

Abstract: Participants showed interest in using apps for managing their asthma, yet recommended improvements on current design. Whereas national figures point to a more ubiquitous mobile device environment, implementation efforts must respond to participants' recommendations while minding lingering digital divides. Currently available apps lack appealing components that teens seek or desire. Subsequent development should include teens' participation in component design insights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…The importance of users´ feedback has been underlined by the outcome of a project including adolescent volunteers (13‐18 years old) who evaluated two asthma apps (AsthmaMD and Asthma Pulse) . The suggested improvements included push reminders (to take medication and to purchase refill), asthma‐related games, fun factors, and a built‐in flow meter .…”
Section: Mhealth In Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of users´ feedback has been underlined by the outcome of a project including adolescent volunteers (13‐18 years old) who evaluated two asthma apps (AsthmaMD and Asthma Pulse) . The suggested improvements included push reminders (to take medication and to purchase refill), asthma‐related games, fun factors, and a built‐in flow meter .…”
Section: Mhealth In Allergic Diseasesmentioning
confidence: 99%
“…7 The importance of users´ feedback has been underlined by the outcome of a project including adolescent volunteers (13-18 years old) who evaluated two asthma apps (AsthmaMD and Asthma Pulse). 62 The suggested improvements included push reminders (to take medication and to purchase refill), asthma-related games, fun factors, and a built-in flow meter. 63 Recording clinical and functional endpoints (ie, symptoms, FEV1, PEF) on a daily basis, together with allergen and pollutant exposure, facilitates continuous asthma monitoring.…”
Section: Asthmamentioning
confidence: 99%
“…While most previous mobile asthma applications (apps) have focused on these aspects of mobile health [9], much of the information captured is typically through e-diaries and self-reports rather than automated sensor-based data collection. Moreover, a recent review [10] demonstrated that the absence of passive sensing (i.e., sensors that collect observations without involving people in the loop) and reliance on e-diaries led to a reduction in compliance and adherence. These observations suggest that there is a need for better integration of wireless sensing capabilities and communication protocols with asthma apps to reduce the amount of e-diary requests from the patient and thus improve adherence and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Teens in Schneider and colleagues’ study [ 27 ] also used existing apps for one week before providing feedback. The two apps investigated were asthma self-management apps available for download by the general public which were tailored to teens.…”
Section: Resultsmentioning
confidence: 99%